2002
DOI: 10.1016/s1631-0691(02)01424-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis on the state of healthiness, quality of the coast and biological resources ‘case of the Moroccan Atlantic coast’ (City of El Jadida)

Abstract: In this study, we present a diagnosis concerning the state of healthiness of the coast of the city of El Jadida by: characterisation of the various collectors rejected in sea without any preliminary treatment, measure of the physicochemical parameters of seawater from sampling stations, evaluation of the concentration of certain heavy metals (Cd, Cu, Zn, Fe and Mn) in four species of algae, which shows that metal contents vary according to the species and the sampling stations, measure of the metal content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 35 publications
2
5
0
2
Order By: Relevance
“…The maximum average concentrations for Al (1215.0 mg/kg), As (14.2 mg/kg) and Li (1.74 mg/kg) were observed in the winter season, while the minimum mean contents for Al (494.9 mg/kg), As (8.74 mg/kg), and Li (1.46 mg/kg) were indicated in the summer period. Similar results have been found by many researchers [23][24][25][26][27][28][29]. Bouthir et al [25] indicated in the Moroccan Atlantic Ocean, higher contents of metallic elements in tissues of M. galloprovincialis during the wet period (winter), whereas lower contents were observed in the hot period (summer).…”
Section: Heavy Metal Analyzessupporting
confidence: 85%
“…The maximum average concentrations for Al (1215.0 mg/kg), As (14.2 mg/kg) and Li (1.74 mg/kg) were observed in the winter season, while the minimum mean contents for Al (494.9 mg/kg), As (8.74 mg/kg), and Li (1.46 mg/kg) were indicated in the summer period. Similar results have been found by many researchers [23][24][25][26][27][28][29]. Bouthir et al [25] indicated in the Moroccan Atlantic Ocean, higher contents of metallic elements in tissues of M. galloprovincialis during the wet period (winter), whereas lower contents were observed in the hot period (summer).…”
Section: Heavy Metal Analyzessupporting
confidence: 85%
“…Concerning the iron content in the sample of mussels taken is of the order of 13.5 mg/kg. The Fe content is lower than those found in the literature for the same species of the order of 2462 mg/kg [8] and other species of bivalves such as Scrabicularia.plana (1657-3-4452mg/kg) [9], Cardium.edule (950-1026 mg/kg) [10] and Mytilus edulis (1380 mg/kg) [11].…”
Section: Heavy Metalsmentioning
confidence: 62%
“…According to the data described in previous reports (Morgan et al 2003;Shiber and Washburn 1979 ), particularly for the Cd, Cu, Fe, Mn and Zn metal contents, and using these new values as a guide, it became clear that most stations in the city of Bou Ismaïl can be considered as having high levels of contamination and, hence, severe pollution by metal trace element (ETM). The significant levels of cadmium obtained in the algae collected could be attributed to the abundance of this metal in the industrial effluent emissions (Kaimoussi et al 2002(Kaimoussi et al , 2004. Although the content of metals in algae was subject to large variations, a trend towards higher levels of mercury than other metals was observed along the coast of the town of Bou Ismaïl, which is in agreement with previous studies using algae.…”
Section: Study Of Heavy Metals In Sediment and Algaementioning
confidence: 99%